A longitudinal investigation of COVID‐19 pandemic experiences and mental health among university students. (30th November 2021) - Stamatis, Caitlin A.; Broos, Hannah C.; Hudiburgh, Stephanie E.; Dale, Sannisha K.; Timpano, Kiara R.
Abstract : Objectives: Previous studies have established a link between the COVID‐19 pandemic and poor mental health. They further suggest that young adults may be especially vulnerable to worsened mental health during the pandemic, but few studies have investigated which specific aspects of the COVID‐19 experience affect psychological well‐being over time. To better understand concrete predictors of poor mental health outcomes in this population, we identified several pandemic‐related experiences and evaluated their effects on mental health symptoms (depression, anxiety, stress, alcohol, and substance use) in a sample of U.S. college students ( N  = 176). Methods: Both mental health symptoms and pandemic‐related experiences were evaluated at the start of quarantine (March/April 2020, Time 1) and the end of the Spring 2020 semester (May 2020, Time 2). Given the limited literature on specific predictors of mental health during a pandemic, we used elastic net regression, a novel analytic method that helps with variable selection when theoretical background is limited, to narrow our field of possible predictors. Results: While mental health symptoms were elevated at both timepoints, there were no clinically significant changes from Time 1 to Time 2 and few differences between sociodemographic groups. Both disruption due to the pandemic ( β  = .25, p  = .021) and limited confidence in the federal government's response ( β  = −.14, p  = .038) were significant predictors of depression symptoms at the end of the semester, even when controlling for baseline depression. Further, predictions that the pandemic would continue to impact daily life further into the future were linked with pandemic stress response symptoms ( β  = .15, p  = .032) at Time 2, beyond the effects of baseline symptoms. Alcohol ( β  = −.22, p  = .024) and substance use ( β  = −.26, p  = .01) were associated with reduced adherence to COVID‐19 guidelines. Conclusions: Our findings indicate that specific aspects of the pandemic experience may be influencing internalizing symptoms and alcohol/substance use in college students, pointing to potential avenues for targeted support and intervention. Practitioner points: A range of factors may influence university student mental health during the COVID‐19 pandemic. Students who expect the pandemic will continue to impact daily life further into the future maybe more likely to report stress symptoms. Disruption due to the pandemic and limited confidence in the federal government's response may be associated with depression symptoms. Alcohol and substance use are associated with lower COVID‐19 guideline adherence in university students.